1999
DOI: 10.1073/pnas.96.25.14641
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of thioredoxin h leads to enhanced activity of starch debranching enzyme (pullulanase) in barley grain

Abstract: Biochemically active wheat thioredoxin h has been overexpressed in the endosperm of transgenic barley grain. Two DNA constructs containing the wheat thioredoxin h gene (wtrxh) were used for transformation; each contained wtrxh fused to an endospermspecific B1-hordein promoter either with or without a signal peptide sequence for targeting to the protein body. Twenty-two stable, independently transformed regenerable lines were obtained by selecting with the herbicide bialaphos to test for the presence of the bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(87 citation statements)
references
References 28 publications
3
83
1
Order By: Relevance
“…Redox control of AGPase in Solanum tuberosum (potato) tubers has been proposed recently (Fu et al, 1998), and further work demonstrated that this phenomenon is relatively widespread and includes photosynthetic and nonphotosynthetic tissues from other species (Tiessen et al, 2002;Hendriks et al, 2003). There also is evidence for redox regulation of pullulanase-type DBEs in several tissues, including Spinacia oleracea (spinach) leaves and the endosperms of Hordeum vulgare (barley) and maize (Beatty et al, 1999;Cho et al, 1999;Schindler et al, 2001).…”
Section: ª 2004 American Society Of Plant Biologistsmentioning
confidence: 96%
“…Redox control of AGPase in Solanum tuberosum (potato) tubers has been proposed recently (Fu et al, 1998), and further work demonstrated that this phenomenon is relatively widespread and includes photosynthetic and nonphotosynthetic tissues from other species (Tiessen et al, 2002;Hendriks et al, 2003). There also is evidence for redox regulation of pullulanase-type DBEs in several tissues, including Spinacia oleracea (spinach) leaves and the endosperms of Hordeum vulgare (barley) and maize (Beatty et al, 1999;Cho et al, 1999;Schindler et al, 2001).…”
Section: ª 2004 American Society Of Plant Biologistsmentioning
confidence: 96%
“…Finally, the protein disulfide reductase thioredoxin has been proposed to regulate the amylolytic system in barley seeds by reduction of disulfide bonds in enzymes and inhibitors (Cho et al 1999). Barley contains two thioredoxin isoforms as well as two isoforms of an NADPH-dependent thioredoxin reductase that reduce the disulfide formed in the thioredoxin active site motif CXXC after it has reduced a target protein disulfide bond (Maeda et al 2003;Shahpiri et al 2008).…”
Section: New Roles and Diversity Of α-Glucan-active Enzymes In Biologmentioning
confidence: 99%
“…After centrifugation for 15 min at 14,000 rpm at 4°C on an Eppendorf 5415C centrifuge (Hamburg, Germany), the supernatant was stored on ice before assaying for protein 2 (by the Coomassie Blue dyebinding assay with gamma globulin as standard) and thioredoxin 4 . The latter involves separation of proteins by sodium dodecyl sulfate polyacrylamide gel electrophoresis, with a positive thioredoxin control from transgenic barley followed by Western blotting.…”
Section: Measurement Of Thioredoxinmentioning
confidence: 99%
“…It was shown that over-expression of thioredoxin in barley greatly enhanced the level of LD expressed in the barley 4 . It was concluded that stimulation could not be traced to the reduction and inactivation of the inhibitor and it was suggested that the mechanism was either an increase in the de novo synthesis of the enzyme or by a promotion of the release of the enzyme from binding.…”
Section: Introductionmentioning
confidence: 99%